Ankle syndesmotic injury: Tightrope vs screw fixation, A clinical academic survey. (September 2021) - Shafiq, Hassan; Iqbal, Zafar; Khan, Mohammad Noah Hasan; Rasool, Muhammad Umer; Faraz, Ahmad; Jamshed, Muhammad Hamzah; Khan, Basharat Ghafoor
Abstract: Objective: The goal of the study is to find out the treatment of choice for ankle fractures involving syndesmotic injury based on level of experience of orthopaedic surgeons. Methods: A survey was undertaken to analyse the management used for ankle fractures with syndesmotic injuries AO 44c in a 35-year-old patient. Surgeons attending an orthopaedic course were invited to take part in a survey sorted into groups: junior surgeons middle grades, and experienced. Pictures of an x ray were shown to the participants and treatment options were asked. Results: 100 surgeons from 20 nations took part in the event. Juniors made up 39%, registrars made up 38%, and experienced doctors were 29%. Screws, were reported by 93% for syndesmosis fixation. 66% of surgeons who used screws for syndesmosis fixation favoured a single screw over two screws.3-4 cortices were virtually evenly divided in choice, with 54% preferring three and 46% preferring four cortices. Only 22% of the time did they utilise a washer with their screws. With 52% of patients, the most typical time for permitting them to weight bear was 4–6 weeks after surgery. At 1–2 months postoperatively, 34% preferred to remove the screw, and at 2-3 months postoperatively, 29% preferred to remove the screw. Conclusion: Data show that the majority of junior level doctors handle their patients according to AO principles. The majority prefer one 3.5 mm screw positioned between 2 and 4 cm above the ankle joint, with three cortices being somewhat preferred. Despite the lack of data to support one procedure, the majority of people remove their screws within 1–3 months Highlights: Various techniques have been described in literature for fixation of ankle fractures with syndesmotic injury. To assess the management of AO 44c syndesmotic injury, a survey of participants at an international AO course was done. The goal is to identify the treatment of choice based on surgeon's experience to treat ankle fracture with syndesmotic injury.